2021
DOI: 10.1111/idh.12497
|View full text |Cite
|
Sign up to set email alerts
|

Dental plaque control strategies for the elderly population: A scoping review

Abstract: Objective: To review the scientific literature and identify dental plaque control strategies focussed on elderly people that improve plaque indices. Design: Scoping review (Joanna Briggs protocol).Data sources: Individual search strategies developed for six databases. The selection of the manuscripts in two phases: title and abstract review, and complete review. Eligibility criteria: Studies on interventions for plaque control in elderly people (60y+).Epidemiological studies and those focussed on caregivers, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 57 publications
0
13
2
Order By: Relevance
“…Gingival inflammation and bleeding were observed in 40 and 41% of the participants, respectively, which was a far lower proportion than those who presented visible biofilm (Figure 1), probably indicating biofilm formation during the hospitalization period. A recent review identified educational, exclusively mechanical, exclusively chemical and chemo-mechanical interventions to prevent biofilm accumulation in elderly people (Ruiz Núñez et al, 2021). Professional brushing, educational strategies that included demonstration, sugarless chewing gum and chlorhexidine mouthrinses were found promising, but with short lasting results (Ruiz Núñez et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gingival inflammation and bleeding were observed in 40 and 41% of the participants, respectively, which was a far lower proportion than those who presented visible biofilm (Figure 1), probably indicating biofilm formation during the hospitalization period. A recent review identified educational, exclusively mechanical, exclusively chemical and chemo-mechanical interventions to prevent biofilm accumulation in elderly people (Ruiz Núñez et al, 2021). Professional brushing, educational strategies that included demonstration, sugarless chewing gum and chlorhexidine mouthrinses were found promising, but with short lasting results (Ruiz Núñez et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…A recent review identified educational, exclusively mechanical, exclusively chemical and chemo-mechanical interventions to prevent biofilm accumulation in elderly people (Ruiz Núñez et al, 2021). Professional brushing, educational strategies that included demonstration, sugarless chewing gum and chlorhexidine mouthrinses were found promising, but with short lasting results (Ruiz Núñez et al, 2021). Also, mouthrinses are adjuncts of oral hygiene that present different active principles and mechanisms to act on reduction of gingivitis (Figuero et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…As well as being essential to prevent the accumulation of denture plaque that may harbour potential pathogens, good denture hygiene is also required to limit malodour, and maintain good aesthetics in denture wearers (Jagger and Harrison 1995). There is a wide range of denture hygiene products and protocols available for denture cleaning (Ruiz N uñez et al 2022). The UK National Health Service recommends that dentures are cleaned as Indeed, in the first randomized double-blinded control trial it was shown that frequent daily denture cleansing with a tablet and brushing was more effective than intermittent cleaning, significantly reducing microbial numbers in denture plaque (Ramage et al 2019).…”
Section: Dental Hygiene and Treatmentmentioning
confidence: 99%
“…There is a wide range of denture hygiene products and protocols available for denture cleaning (Ruiz Núñez et al . 2022). The UK National Health Service recommends that dentures are cleaned as often as normal teeth (i.e.…”
Section: Dental Hygiene and Treatmentmentioning
confidence: 99%
See 1 more Smart Citation